Nasal disease and quality of life in athletes. Issue 9 (31st August 2018) - Walker, A C; Surda, P; Rossiter, M; Little, S A
Abstract: Objectives: Nasal disease imposes a significant disease burden upon the individual in the general population, but is relatively under studied in athletes. This study sought to define the frequency of nasal symptoms in the active population, and to quantify the impact of these symptoms on quality of life and on the frequency of upper respiratory tract infections. Results: A total of 296 participants completed the study (246 athletes and 50 sedentary controls). Nasal symptoms were significantly more frequent in the active group than in the sedentary controls (70 per cent vs 52 per cent). Upper respiratory tract infections were significantly more common in athletes with regular nasal symptoms than in athletes without nasal symptoms. Quality-of-life scores, as measured by the 22-item Sino-Nasal Outcome Test, were significantly worse in athletes with regular nasal symptoms. Conclusion: This study suggests that regular exercise is associated with a significant increase in the prevalence of troubling nasal symptoms, and nasal symptoms in athletes are associated with increased susceptibility to upper respiratory tract infections. Quality of life was negatively affected, confirming the importance of nasal health to athlete welfare.